CLINICAL AND IMMUNOLOGICAL CHARACTERISTICS OF PATIENTS TREATING WITH BOTULOTOXIN A IN DYNAMICS - V. V. Khodachenko; L. P. Sizyakina; O. A. Sidorenko (Медицинский вестник Юга России, 2014)
Purpose: To investigate the dynamic changes of immune system in aesthetic patients treated with botulinum toxin type A. Materials and methods: The study involved 20 patients treated with botulinum toxin type A to reduce mimic wrinkles.Phenotypic and functional characteristics of immune cell were investigated during the study. Immune parameters were discovered before and in 14 and 90 days after injections with standard immunological methods as a flow cytometry, immunodiffusion in Manchini test and enzyme immune test.Results: During the study a positive clinic aesthetic effect and differences in immune status were observed in all patients. Parameters of immune system in 2 weeks after injection were characterized by increasing of immune suppression, rising cytotoxic activity of T-cells and activation of IF-γ synthesis. It results in overweight of antiinflamatory cytokines compared with proinflamatory cytokines. These changes have been kept for 3 months with a tendency to increasing of intracellular cooperation and IF-γ synthesis.Summary: In patients effectively treated with botulinum toxin injections there are different immune changes. It shows a physiological reaction of immune system to the introduction of heterogenous antigens.